SOME HIGHLIGHTS IN SAUDI ARABIA–US RELATIONSHIP IN THE PERIOD 2011-2020 - Phuong, Hoang Thi Mai (VNU Journal of Foreign Studies, 2021)
Saudi Arabia - US relationship has long been known as a strategic alliance, despite the differences between a monarchy and a constitutional republic. So far, Saudi Arabia has been one of the closest allies, the strongest economic partner and an important strategic partner of the US in the Middle East. Even so, the relationship between Saudi Arabia and US has also experienced such ups and downs as the 1973 oil embargo, the terrorist event in the US on 11st September or the political and social crisis in the North Africa - Middle East region that took place in late 2010 and early 2011 (also known as the "Arab Spring"), the assassination of journalist Jamal Khashoggi at the Saudi Embassy in Turkey and the attack on the oil field in Saudi Arabia on 14th September, 2019, enormous impacts on the Middle East - North Africa and the world situation. The article briefly summarizes some prominent issues in the Saudi-US relationship between 2011 and 2020. Besides, the article also analyzes the factors that are likely to affect the Saudi-US relationship and some forecasts for the development direction of this relationship in the coming time. The article uses the international relations research methods, analytical methods to synthesize and evaluate, case study method, system-structured method, forecast and evaluation method to objectively evaluate this relationship.